Diseño para la obtención de aceite esencial con base al aprovechamiento de la semilla del aguacate utilizando diferentes especies (2022)
The following research project has as its objective the extraction of oil from the avocado seeds of three different varieties, which were selected from a review in the literature, where they were chosen; the Lorena, Hass and Criollo variety, based on the fact that within their genus (PERSEA AMERICANA MILL) they present a higher content of fats, terpenes and polyphenols compared to the other varieties. Based on this, an experimental methodological design was proposed for the extraction of oil from the seeds of these varieties, where the selection of the extractive method and the solvent was implemented through two qualitative selection matrices and through reviews of tests that sustain. The solid-liquid extraction was decanted using the Soxhlet method and using the 95% ethanol solvent. Using a ratio of 1:10, this experimentation yielded yields of: 4.02% in the Lorena variety, 10.05% in the Hass variety, and 5.57% in the Criolla variety. Within the experimentation, other properties such as humidity, dry matter, and seed ash were also analyzed.